2021
DOI: 10.1111/are.15147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fish oil replacement by poppy seed oil on growth performance and fillet quality of rainbow trout (Oncorhynchus mykiss)

Abstract: Rainbow trout (Oncorhynchus mykiss) were fed replacement of fish oil with diets including poppy seed oil (PSO; 0%, 50% and 100%). At the end of the 90‐day feeding period, the water holding capacity of the fillets decreased when the storage time increased. The colour and pH values were affected by both storage and diets. The hardness, springiness, gumminess and chewiness index of the fillet samples decreased as a consequence of increasing storage time, whereas the cohesiveness values of the fillets increased. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Te quantity of linoleic acid in the diet raised signifcantly (P < 0.05) as the fraction of poppy seed oil in the feed increased (Table 1). Te combination of poppy seed oil with fsh oil in rainbow trout feeds increased growth performance, according to a study on the growth performance and fesh quality of trout [7]. Te current study yielded similar results; it was observed that increasing the quantity of poppy seed oil in the experimental diet formulation improved carp growth and feed utilization performance.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Te quantity of linoleic acid in the diet raised signifcantly (P < 0.05) as the fraction of poppy seed oil in the feed increased (Table 1). Te combination of poppy seed oil with fsh oil in rainbow trout feeds increased growth performance, according to a study on the growth performance and fesh quality of trout [7]. Te current study yielded similar results; it was observed that increasing the quantity of poppy seed oil in the experimental diet formulation improved carp growth and feed utilization performance.…”
Section: Discussionsupporting
confidence: 68%
“…In recent years, the use of substitute options for fsh oil has become a very important topic because fsh oil is widely utilized as a human nutritional supplement and in the ration of many farm animal diets, particularly poultry [3]. For that reason, various research studies have focused on plant-origin oils as a possible replacement for fsh oil in aquafeeds [4][5][6][7][8]. Studies and industrial trends suggest that fsh oil inclusion rates in aquafeeds have decreased as a result.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fish, feed compositions, such as dietary fatty acids, are the main factors for flesh quality . In the studies of Atlantic salmon (Salmo salar) and golden pompano (Trachinotus ovatus) rainbow trout (Oncorhynchus mykiss), the fish oil or moderate n -3 PUFA diet intake is beneficial to the improvement of fillet edible quality and texture. In the present study, muscle texture measures, including tenderness, hardness, adhesiveness, chewiness, and gumminess, in fish fed diets D2 and D3 are significantly higher than the other dietary groups. The results demonstrated that diets D2 and D3 with LA/ALA ratios of 6 and 3, respectively, are also conducive to the muscle texture of farmed tilapia.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, 328 articles were included in this research (Figure 1) and their detailed information is stored in Table S1. Among all the included articles, 73 were conducted on Oncorhynchus mykiss , 4,23,38–108 67 were about Salmo salar , 109–175 36 were for Oreochromis niloticus , 176–211 27 investigated Sparus aurata ,…”
Section: Methodsmentioning
confidence: 99%